Chodzenie ze sobą, spanie ze sobą, mieszkanie ze sobą. Młodzieńcze relacje uczuciowe i obyczajowość przedślubna - Iwona, Przybył (Wydawnictwo Naukowe UAM, 2010)
The aim of this article concentrates on the presentation of what do young Polish people mean by the term marriage and what is their acceptation for premarital sexual behaviors and premarital cohabitation. The author tries to answer are there typical dating and courtship development patterns and how do changes of the premarital customs, like having sexual relations, affect future relations between wives and husbands. This paper is based on literature and the results of the author's study carried out in 2007 and 2008.
Dating, coupling, living together. Emotional relationships and the premarital customs